2008
DOI: 10.1007/s00216-008-2001-4
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive and nondestructive NMR, Raman and XRF analysis of a Blaeu coloured map from the seventeenth century

Abstract: A complete multianalytical study of a hand-coloured map from the seventeenth century is presented. The pigments atacamite, massicot, minium, gypsum, carbon black and vermilion were determined by means of XRF and Raman spectroscopy. The state of conservation of the cellulosic support was monitored by means of unilateral NMR. The analysis was nondestructive and noninvasive, and thus several spectra were collected from the same areas, yielding more reliable results without damaging the artwork. The role of copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Raman spectroscopy has been used to analyse cellulose-based materials such as artworks on paper supports, [25] historical maps [26] and historical textiles [27] because the Raman features of the inorganic compounds accompanying the cellulose support appear at completely different wavenumbers.…”
Section: Samplementioning
confidence: 99%
“…Raman spectroscopy has been used to analyse cellulose-based materials such as artworks on paper supports, [25] historical maps [26] and historical textiles [27] because the Raman features of the inorganic compounds accompanying the cellulose support appear at completely different wavenumbers.…”
Section: Samplementioning
confidence: 99%
“…They could correspond to atacamite (CuCl 2 · 3Cu(OH) 2 ) with characteristic strong bands at 514, 3353 and 3437 cm −1 [26,36] although other bands of weak to medium intensity at 819, 912 and 974 cm −1 can hardly be detected in our spectra due to the weakness of the signal and the strong fluorescence background. Despite the fact that this kind of copper salt was mentioned in old treatises, [26] there is no agreement in scientific literature whether copper chlorides were used as raw materials [37,38] or whether they must be attributed to degradation processes from other copper pigments like azurite. [39] Here, the presence of Cl exclusively in this pictorial layer and its homogenous distribution suggested the intentional application of a chloride-containing pigment or a pigment mixture.…”
Section: Red Areasmentioning
confidence: 99%
“…Raman spectroscopic analysis did not reveal the presence of calcium carbonate nor calcium sulphate due to problems of fluorescence. EDXRF analysis also showed that there was a noticeable amount of calcium present in the samples, even though it was lower than that previously found with the analysis of similar samples [36]. Taking into account that the molar ratio Ca/S was different from that of 1:1 (Table 1), the use of calcium sulphates should be ruled out.…”
Section: Detecting Fillersmentioning
confidence: 68%